Pratylenchus speijeri n. sp. (Nematoda: Pratylenchidae), a new rootlesion nematode pest of plantain in West Africa - Luca, F. de; Troccoli, A.; Duncan, L.W.; Subbotin, S.A.; Waeyenberge, L.; Coyne, Danny L.; Brentu, F.C.; Inserra, R.N. (Brill, 2012)
A new root-lesion nematode, particularly pathogenic to Musa spp. and causing important plantain losses in Ghana, is described and named Pratylenchus speijeri n. sp. The cryptic status of this species within the P. coffeae species complex has been assessed and confirmed in this study. An extensive comparison of the morphological and molecular characteristics of this new species with those of P. coffeae and other related amphimictic species did not result in an unambiguous separation of this species from P. coffeae because only a few morphological features of diagnostic value were found. Sequence and phylogenetic analyses of the D2-D3 expansion segments of the 28S rRNA gene, the ITS rRNA gene and a portion of the hsp90 gene of P. speijeri n. sp. and P. coffeae species complex populations from different sources generated majority consensus BI trees with three major clades: P. speijeri n. sp. from Musa spp. roots in Ghana; unidentified or putative new Pratylenchus sp. C1 from Colocasia esculenta roots in Japan and P. coffeae with non-homogeneous relationships from different hosts and distant geographical areas. These results confirmed the validity of P. speijeri n. sp. as a new taxon and indicated that P. coffeae populations from Colocasia in Japan also need to be considered as a new species. Sequence differences in the ITS were used to design group- and species-specific primers to detect P. speijeri n. sp. and other species of P. coffeae species complex. The use of these species-specific primers for the separation of P. speijeri n. sp., Pratylenchus sp. C1 and P. coffeae has important practical application in breeding programmes for agriculture in West Africa.